(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The overall goal of the Decade of Education for Sustainable Development 2005-2014, as proclaimed by the United Nations, is to integrate the principles, values and practices of sustainable development into all aspects of education and learning. This integrated and multi-dimensional approach is supported in South Africa by the White Paper for Education and Training and the National Curriculum Statement (NCS) for History as part of the Social Science learning area. !e aim of this article is to report on how a historicalenvironmental approach to education had been realised in the context of Eenheid primary school in Nylstroom (Modimolle) located on grounds used for a concentration camp during the South African War (October 1899 to May 1902). In particular, the researchers wanted to establish how a diverse group of learners experienced and internalised their historical-environmental events in creating their present identity. The findings of the school’s learners (n=51) who participated in a case study suggest that the historical memory which developed from the unique location of the school not only expanded the learners perspectives on intercultural understanding, but also contributed to a better appreciation and responsibility of environmental and socio-cultural issues in a post-apartheid South Africa. In the process an ethic of sustainable living and the creation of a “new” South African identity developed.